Moon spinners - Goldenbaum, Sally (Goldenbaum, Sally. Seaside knitters mystery., 2010)
In a quaint fishing village the Seaside Knitters want to help their friend, Gracie, open a café, but instead find themselves stitching together clues when Gracie's aunt is murdered.